Wind of change: Exploring the value creation of diaconia - Hellöre, Lise-Lotte (Approaching Religion, 2023)
The value of diaconia is difficult to measure, its immaterial assets not easily grasped. In this article, I contribute to the area in analysing the perspective of 22 deacons on what is most important in their job and what could potentially be of greatest value if there were no restrictions of money and other resources. Data were collected in the midst of the Corona crisis in 2021 in the Porvoo diocese in the Evangelical Lutheran Church of Finland. The timing of data collection therefore coincides with a unique chance to rethink ways of doing things. International research shows that the religious heritage of diaconia has changed from merely supporting people in need to also advocating marginalized groups and building bridges to other actors. This intangible heritage is sensitive to changes in society, whereby latent sources of value creation may be traced. Key contributions are identifying new areas of development of this religious heritage and assessing the value creation taking place – now and in a potential future. For this, understanding the changed role of diaconia in society and in the church are central.